Running the Numbers for the Path of Mantra: Distinguishing the Thirteenth Bhūmi in Fifteenth-Century Tibet - Dachille, Rae (Religions, 2021)
This article explores a Buddhist text in which numbers set the very stakes for liberation. In 1404, Ngor chen Kun dga’ bzang po (1382-1456), who was to become one of the most esteemed tantric commentators of the Tibetan Sakya tradition, composed his first polemical text, Dispelling Evil Misunderstandings of the Explanation of the Ground of Zung ‘jug Vajradhara. In this early work, Ngor chen grapples with the relationship between the path of perfections and of secret mantra as conduits to liberation. I illuminate the ways in which ritual, exegesis, and pedagogy converge in Ngor chen’s text to reveal larger implications for distinguishing the eleventh and thirteenth grounds (bhūmi) of Buddhahood in fifteenth-century Tibet. In concluding, I highlight the art of differentiation as a fundamental Tibetan scholastic enterprise and briefly engage Ngor chen’s acts of distinguishing sūtra and tantra in conversation with those of key Tibetan predecessors and contemporaries.